Students' Grammatical Error in Using Present Tense - Muhassin, Mohammad; Hayrunnisa, Nadya Rizky; Pradana, Satria Adi (English Education: Jurnal Tadris Bahasa Inggris, 2019)
Students’ error analysis is very important for helping English as a Foreign Learners’ (EFL) teachers to develop their teaching materials, assessments and methods. The study aims to describe and analyze the students’ grammatical error in the use of  simple present tense, and the cause of errors by the eleventh grade students of Senior High School (SMAN)  4 Bandar Lampung in the  school year of 2018/2019. This is a kind of descriptive qualitative study, in which the data consisted of students’ sentences containing errors in the use of simple present in the text of analytical exposition, viewed from Linguistic Category Taxonomy (LCT). The study discovers that there are five types of errors based on LCT. They are errors of noun phrase, verb phrase, verb-and-verb construction, word order and transformation. Moreover, the causes of error most widely performed are subsequently  performance fault, overgeneralization, markers of transitional competence, teacher-induced error, scheme of communication and assimilation, interference.